(untitled) (Sambahak: Human Rights Journal, 2024)
In a democracy, the role of advocates as guardians of justice cannot be overstated. Lawyers are recognized as the professional in the field of law. They argue for the cause of another person in front of any judicial authority. A fearless legal profession is the cornerstone of a thriving democracy. They serve as the backbone of the judicial system, tirelessly advocating for the rights of their clients and upholding the principles of fairness and equality before the law. In the pursuit of justice, lawyers are the first line of defense for human rights. However, in many parts of the world, including Nepal, these legal professionals often find themselves subjected to threats, intimidation, attacks, which hindering their ability to perform duties effectively. This article delves into the pressing need for an Advocate Protection Law in Nepal, drawing inspiration from the Advocates Protection Act of India. Examining the challenges faced by Nepalese advocates and analyzing the Indian legislation, it underscores the urgency for a comprehensive legal framework to safeguard the interests of those who defend justice. Additionally, the article calls upon the Nepalese parliament and the Nepal Bar Council to undertake proactive measures in drafting and enacting such a law, ensuring that the guardians of justice are shielded from undue interference and can carry out their noble duties without fear or favor.